On the origin of PRDM9-guided recombination hotspots - Francisco Úbeda; Reinhard Bürger; Frederic Fyon (Proceedings of the National Academy of Sciences, 2026)
Meiotic recombination is highly conserved across vertebrates and plays an essential role in ensuring chromosomal segmentation and generating genomic variation. However, species employ two strikingly different mechanisms to guide recombination. In most mammals, recombination hotspot locations are determined by the protein PRDM9, which binds specific DNA sequence motifs. These motifs are rapidly eroded by biased gene conversion, rendering this mechanism self-destructive and evolutionarily transient. In contrast, birds initiate recombination at open chromatin regions independently of sequence motifs, producing self-preserving and evolutionarily stable recombination hotspots. Some species use both types of hotspots simultaneously, raising the unresolved question of why PRDM9-guided hotspots persist alongside a robust alternative. Here, we address this problem using a population genetic model that explicitly considers competition between PRDM9-guided and non-PRDM9-guided recombination hotspots. We show that non-PRDM9-guided hotspots are generally favored because, lacking sequence specificity, they generate more crossovers required for proper chromosome segregation. However, PRDM9-guided hotspots can overcome this disadvantage when simultaneous binding of both homologous chromosomes (symmetric binding) is more likely to resolve as crossovers than binding of a single homolog (asymmetric binding). Although PRDM9 reduces overall crossover rate, its sequence specificity increases the probability of symmetric binding within hotspots, creating a trade-off that can favor PRDM9 under specific selection regimes. Our model predicts that PRDM9-dependent species are particularly sensitive to disruptions of symmetric binding, whereas species lacking PRDM9 are more vulnerable to complete crossover failure. Intermediate regimes allow stable coexistence of both hotspot types.